Potential of Yeasts as Biocontrol Agents of the Phytopathogen Causing Cacao Witches’ Broom Disease: Is Microbial Warfare a Solution? - Ferraz, Pedro; Cássio, Fernanda; Lucas, Cândida (Frontiers in Microbiology, 2019)
Plant diseases caused by fungal pathogens are responsible for major crop losses worldwide, with a significant socio-economic impact on the life of millions of people who depend on agriculture-exclusive economy. This is the case of the Witches’ Broom Disease (WBD) affecting cacao plant and fruit in South and Central America. The severity and extent of this disease is prospected to impact the growing global chocolate market in a few decades. WBD is caused by the basidiomycete fungus Moniliophthora perniciosa. The methods used to contain the fungus mainly rely on chemical fungicides, such as copper-based compounds or azoles. Not only are these highly ineffective, but also their utilization is increasingly restricted by the cacao industry, in part because it promotes fungal resistance, in part related to consumers’ health concerns and environmental awareness. Therefore, the disease is being currently tentatively controlled through phytosanitary pruning, although the full removal of infected plant material is impossible and the fungus maintains persistent inoculum in the soil, or using an endophytic fungal parasite of Moniliophthora perniciosa which production is not sustainable. The growth of Moniliophthora perniciosa was reported as being antagonized in vitro by some yeasts, which suggests that they could be used as biological control agents, suppressing the fungus multiplication and containing its spread. Concurrently, some yeast-based products are used in the protection of fruits from postharvest fungal spoilage, and the extension of diverse food products shelf-life. These successful applications suggest that yeasts can be regarded a serious alternative also in the pre-harvest management of WBD and other fungal plant diseases. Yeasts’ GRAS (Generally Recognized as Safe) nature adds to their appropriateness for field application, not raising major ecological concerns as do the present more aggressive approaches. Importantly, mitigating WBD, in a sustainable manner, would predictably have a high socioeconomic impact, contributing to diminish poverty in the cacao-producing rural communities severely affected by the disease. This review discusses the importance/advantages and the challenges that such a strategy would have for WBD containment, and presents the available information on the molecular and cellular mechanisms underlying fungi antagonism by yeasts.